Analysis of Green Accounting Implementation on Environmental Disclosure and Corporate Reputation - Ekayana Sangkasari Paranita; Anisa Putri; Muhamad Syafii (Mandalika Journal of Business and Management Studies, 2026)
The persistent gap between sustainability rhetoric and tangible reputational outcomes necessitates examining the mechanisms linking environmental accounting to stakeholder perceptions. This study aims to analyze the mediating role of Environmental Disclosure in the relationship between Green Accounting implementation and Corporate Reputation. Utilizing a qualitative library research method, this investigation systematically synthesizes evidence from scholarly journals, authoritative textbooks, and empirical reports through rigorous content analysis. The findings reveal that substantive Green Accounting generates credible, auditable metrics that significantly enhance disclosure integrity. However, the positive effect on reputation is strictly conditional; disclosures lacking robust accounting foundations provoke greenwashing accusations and severe reputational penalties. Crucially, Environmental Disclosure acts as a full mediator, effectively converting internal accounting data into external reputational signals only when characterized by transparency, quantifiability, and external assurance. This research enriches Stakeholder and Signaling theories by identifying accounting system maturity as the pivotal contingency factor. The implications emphasize that firms must prioritize authentic accounting integration over symbolic reporting to achieve sustainable competitive advantages amidst tightening mandatory sustainability reporting frameworks.